KONSUMSI DAN DAYA TERIMA PASIEN RAWAT INAP PENYAKIT KARDIOVASKULAR TERHADAP MAKANAN YANG DISAJIKAN RSUP H. ADAM MALIK MEDAN - Nadia Chalida Nur; Etti Sudaryati; Ernawati Nasution (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2015)
Cardiovascular disease is a disorder of the heart and blood vessel, included heart disease and stroke. Theraphy for cardiovascular disease can be done by admission to the hospital, receiving medical treatment and supported by proper diet treatment. The efficacy of the diet provided by the hospital can be evaluated by nutrient consumption and food acceptance of the food served. The purpose of this research is to study nutrient consumption and food acceptance among cardiovascular disease hospitalized patients to the food served in Adam Malik General Hospital. A descriptive study was conducted on 32 cardiovascular disease patients based on physician diagnosis. Patient food consumption data obtained using food recall 24 hours form. Univariate data analysis to look at the frequency distribution of consumption levels, the level of adequacy, and acceptability of food served. The result of the research showed the tendency of the intake of food the patient is at the level of the deficit, because the patient is not able to spent the hospital food. The tendency of sufficient levels of nutrients patients are also at the level of the deficit, that can slow the healing process and increase the time of patient care in hospitals. Food acceptance measurement showed that food provided by hospital was well accepted. Consumption of food patients can be stimulated by increasing social atmosphere, good service, and provide a menu option or modify the menu to avoid boredom patients on hospital food served.   Keywords : nutrient consumption, food acceptance, cardiovascular disease